The Destiny of Civilization Finance Capitalism, Industrial Capitalism or Socialism - Hudson, Michael (Islet, 2022)
This book is based on the lecture series on finance capitalism Michael Hudson presented for the Global University for Sustainability. The book explains why the U.S. and other Western economies have lost their former momentum: A narrow rentier class has gained control and become the new central planner, using its power to drain income from increasingly indebted and high-cost labor and industry. The American disease of de-industrialization has resulted from the costs of industrial production being inflated by the economic rents extracted by this class under the system of financialized monopoly capitalism that now prevails throughout the West.
Includes Index
Keywords: Finance capitalism | Industrial capitalism | Socialism